2019
DOI: 10.1016/j.ebr.2019.100344
|View full text |Cite
|
Sign up to set email alerts
|

Anterior thalamic deep brain stimulation in epilepsy and persistent psychiatric side effects following discontinuation

Abstract: We report a case of a patient with drug-resistant epilepsy treated with deep brain stimulation of the anterior nucleus of the thalamus (ANT-DBS). The patient developed psychiatric side effects (PSEs), namely irritability, hostility, aggressiveness, and paranoia, after implantation and stimulation initiation. The stimulation was discontinued and the PSEs were mitigated, but the patient did not return to her pre-implantation state, as documented by repeated psychiatric reports and hospitalizations. To our knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In fact, only 16% of patients report seizure-free interval of at least 6 months, 35.5% develop device-related serious adverse side effects, 37.3% report depression, and 27.3% memory impairment. 47,48 Callosotomies were previously used to treat refractory generalized epilepsy but are less common in current clinical practice. Selective lesions of the callosal fibers that connect the seizure focus for example through the development of noninvasive focused ultrasound and deep brain stimulation to modulate cortico-cortical projections could reduce generalized tonic-clonic seizures and sudden unexpected death in epilepsy (SUDEP) and serve as alternatives to thalamic stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, only 16% of patients report seizure-free interval of at least 6 months, 35.5% develop device-related serious adverse side effects, 37.3% report depression, and 27.3% memory impairment. 47,48 Callosotomies were previously used to treat refractory generalized epilepsy but are less common in current clinical practice. Selective lesions of the callosal fibers that connect the seizure focus for example through the development of noninvasive focused ultrasound and deep brain stimulation to modulate cortico-cortical projections could reduce generalized tonic-clonic seizures and sudden unexpected death in epilepsy (SUDEP) and serve as alternatives to thalamic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, anterior thalamic deep brain stimulation is performed on patients with intractable epilepsy, but it is not always effective. In fact, only 16% of patients report seizure‐free interval of at least 6 months, 35.5% develop device‐related serious adverse side effects, 37.3% report depression, and 27.3% memory impairment 47,48 . Callosotomies were previously used to treat refractory generalized epilepsy but are less common in current clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients showed improvements in anxiety, attention, and executive function compared to baseline. Though, outside of that clinical trial, there has been a reported case of persistent psychiatric side effects during ANT DBS and following discontinuation of ANT DBS (Doležalová et al, 2019 ). For patients with intractable epilepsy receiving vagus nerve stimulation (VNS), the impact on mood appears to be favorable; VNS is an FDA-approved therapy for treatment-resistant depression (Aaronson et al, 2017 ; Chan et al, 2018 ; Elger et al, 2000 ).…”
Section: Rigorous Practices: Confounding Factors and Recommendations For Experimental Designsmentioning
confidence: 99%
“…One report describing a patient with persistent psychiatric adverse events contradicts this belief. 43 Mood disturbances or memory problems observed only in a blinded phase of the SANTE trial may be related to overstimulation of the ANT and a lesional (microthalamotomy) effect. 16 Monopolar stimulation using relatively high stimulation parameters (especially voltage) in an early postoperative phase may explain this transient subjective mood and memory problems.…”
Section: Cognitive and Emotional Sequelae Of Ant Dbsmentioning
confidence: 99%